UNDERSTANDING FACTORS INFLUENCING INTENTION TO ADOPT TELEDENTISTRY IN MOBILE HEALTH APPLICATIONS AND THE IMPACT ON USE BEHAVIOR: EVIDENCE FROM INDONESIAN USERS - Fauzia Nurmawlidina, Mutiara
The COVID-19 pandemic has made massive impacts on the dental healthcare industry. As a disruptive innovation, teledentistry in mobile health applications (TMA) offers features that can solve several problems in unexpected situations, such as preventing virus transmission during dental procedures. TMA can also be a solution to the problem of unequal distribution of dental health service facilities, especially in Indonesia. However, the acceptance of this technology still needs to improve due to several factors. There have yet to be studies that can solve this problem. This study aims to answer the gaps by using the extended unified theory of acceptance and use of technology 2 (UTAUT2) to discover the factors that can improve TMA performance and how these factors can influence users' intentions and use behavior in adopting TMA. The quantitative study collected data through web-based questionnaires from 298 respondents. The researcher employed a partial least square-structural equation model (PLS-SEM) approach for the data analysis. The findings show that facilitating conditions, social influence, and trust in dentists positively and significantly influence the behavioral intention to adopt TMA. Furthermore, facilitating conditions and behavioral intention to adopt TMA positively and significantly influence the use behavior. A qualitative study was also carried out to enrich the findings by interviewing 11 respondents. The themes obtained from the results of the thematic analysis are positive factors and challenges in adopting TMA. The positive factors are efficiency, ease of learning, low prices of consultation fees, adequate resources, social influencers, and trust. Meanwhile, challenges include indirect medical intervention, technical issues, high costs of pharmacy services, and cybercrime threats. The findings of this research provide theoretical and practical implications that are useful for the development and successful commercialization of TMA.